A educação de policiais militares praças, no Brasil contemporâneo (desde 2018): o caso paranaense - Oliveira, Sandra Schons Lemos de (2023)
This dissertation, linked to line of research 2, of the Graduate Program, Master's level, of the State University of Western Paraná - UNIOESTE -, Francisco Beltrão Campus, and entitled: Society, Knowledge and Education, sought to answer questions related to the education directed to military police officers, squares, in the state of Paraná. The study aimed to understand how the Military Police of Paraná, through its higher police school: the Academia Policial Militar do Guatupê, responsible for teaching and educating the Military Police in the state, has been adapting to the growing demands of redemocratization and reformulation of the its formative processes; brought about by the new national public security policy, through Law No. 13,675, of 2018, which created the Single Public Security System and which began to guide the educational processes of military police officers in Brazil. The study was developed through case study. The daily life of the Training Course for Squares held in the year 2021, which took place in Guatupê, was accompanied as a way of entering, more precisely, the daily training of future military police officers, squares. The analysis tools used were the observation of the formative routine; documental analysis and conducting focal interviews with Military Police officers, squares, of the aforementioned training course. It was found that education directed at military police officers, squares, was developed in the midst of a context characterized by the growing and conflicting presence of knowledge/powers that seem to dispute “ideal” models of professional training for the field of public security. There were disciplines and values arising from the operational field (strongly linked to the militarist conformation); there was also the presence of knowledge coming from the legal field; and there was also knowledge from the area of Human and Social Sciences. It is evident that the training of military police, enlisted men, essentially took place within the canons of a legal and militaristic order, demarcated by legal procedures that ratified hierarchy and discipline. Military police education, of the squares, implemented after the implementation of Law nº 13.675/2018, although it has a broader policy character, has been adapted in the micro-social, institutional spheres, in the face of inherited cultural forms. Tensioningthe relationship between what is instituted and the proposals for formative/educational change.